2020
DOI: 10.3390/nano10061133
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Structural-Coloured Carbon Fabrics by Thermal Assisted Gravity Sedimentation Method

Abstract: Structural-coloured poly(styrene-methyl methacrylate-acrylic acid) (Poly(St-MMA-AA)) deposited carbon fabrics (Poly(St-MMA-AA)/PCFs) with fascinating colours (salmon, chartreuse, springgreen, skyblue, mediumpurple) changing with the (Poly(St-MMA-AA) nanoparticle sizes can be facilely fabricated by the thermal-assisted gravity sedimentation method that facilitates the self-assembly of Poly(St-MMA-AA) colloidal nanoparticles to generate photonic crystals. The particle sizes of Poly(St-MMA-AA) copolymer with core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…These functional groups testify the existence of CNPs. [ 22‐23 ] For CVPs, peaks at 3283, 1635, 1541, 1252 cm –1 which are attributed to the characteristic amine group of ovalbumin, and the characteristic peaks of CNPs were not found here (Figure 3c). From these results, it can be concluded that OVA was successfully coated on the surface of the CVPs.…”
Section: Resultsmentioning
confidence: 86%
“…These functional groups testify the existence of CNPs. [ 22‐23 ] For CVPs, peaks at 3283, 1635, 1541, 1252 cm –1 which are attributed to the characteristic amine group of ovalbumin, and the characteristic peaks of CNPs were not found here (Figure 3c). From these results, it can be concluded that OVA was successfully coated on the surface of the CVPs.…”
Section: Resultsmentioning
confidence: 86%
“…It is a colorless, clear liquid at room temperature and miscible with water at any ratio. Acrylic acid is miscible with water at any proportion, and can be miscible with MMA liquid by way of emulsion polymerization reactions 37,38) . In this study, acrylic acid was first mixed with the NAg solvent and then the NAg suspended in acrylic acid was added to the denture base, which did not only increase the dispersion of the NAg in the denture base but also reduced the generation of bubbles, ensuring appropriate mechanical properties of the resulting denture base.…”
Section: Discussionmentioning
confidence: 99%
“…Acrylic acid is miscible with water, alcohols, ethers, and chloroform. With water in any proportion, acrylic acid can be miscible by emulsion polymerization induced reactions with MMA liquid 36,37) .…”
Section: Introductionmentioning
confidence: 99%
“…Selected companies involved in this fast-developing arena include Nano-Tex, Aspen Aerogel, BASF, and Nano-Horizons. In line with this theme, four representative articles [ 1 , 2 , 3 , 4 ] have been published in this Special Issue:…”
mentioning
confidence: 99%
“…As shown by Kan et al [ 1 ], the preparation of poly(styrene-methyl methacrylate-acrylic acid) deposited carbon fabrics (or Poly(St-MMA-AA)/PCFs) with desirable vivid structural colours transforming remarkably from salmon to medium purple (by controlling the Poly(St-MMA-AA) size) was feasible. The concentric shape of Poly(St-MMA-AA), with Poly(MMA-AA) shell and PS core, as well as the chemical composition of the Poly(St-MMA-AA) copolymer, were investigated.…”
mentioning
confidence: 99%